Sądownictwo polskie w Generalnym Gubernatorstwie : refleksje o najnowszej książce Andrzeja Szulczyńskiego - Wrzyszcz, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The monograph discussed in this review article is not a comprehensive synthesis which fully covers the complex issues of the organization and functioning of the Polish judiciary in the General Government during the Second World War. The opinions formulated in the paper are polemical and often critical. However, many of the facts presented by Andrzej Szulczyński are completely new and significantly expand the state of our knowledge. The findings made by the author and the conclusions he formulated in the monograph will constitute an impulse for further research on the judiciary in Poland under German occupation during the Second World War, which I believe is necessary.
Keywords: sądownictwo polskie; Generalne Gubernatorstwo; okupacja niemiecka; druga wojna światowa